Teaching Listening through Video for the Eighth Grade Students of SMP Negri 26 OKU - Hasbullah, Hasbullah (Journal of English and Education (JEE), 2009)
In English language, there are integrated skills to be mastered such as speaking, listening, reading and writing. Listening is the language modality that is used most frequently; however, language learners do not recognize the level of effort that goes into developing listening ability. Therefore, it is essential for language teachers to help students become effective listeners. One of efforts can be done is teaching listening through video.The writer used quasi-experimental method with two groups' pre-test, posttest design. The independent variable of this research is the use of video and the dependent variable is the students' listening ability. In this research, the population is all the eighth grade students of SMP Negeri 26 OKU, in academicyearsof2009-2010. AH of the populations are taken as samples of investigation. The data of this study collected by means of written test.The results show that the students from the experimental group used video has better achievement in learning asking and giving direction than the students from control group. There was a significant difference in teaching listening through video and not using video. Therefore, it can be concluded that teaching listening through video was more effective than CD to the eighth students of SMP Negeri 26 OKU.